How to file for chapter 7 bankruptcy - O'Neill, Cara (Lawyer); Renauer, Albin (Berkeley, California Nolo, 2019)
Written in an easy-to-understand manner, How to File for Chapter 7 Bankruptcy does more than help a reader determine whether filing for Chapter 7 bankruptcy makes sense. The step-by-step instructions allow the reader to prepare and file a bankruptcy case without a lawyer.
Should you file for chapter 7 bankruptcy? -- The automatic stay -- Your property and bankruptcy -- Your house -- Secured debts -- Complete and file your bankruptcy paperwork -- Handling your case in court -- Life after bankruptcy -- Which debts are discharged -- Help beyond the book.
Includes index.
108509
Keywords: Bankruptcy -- United States; Chapter 7; United States; Law for laypersons; Popular works; Law for laypersons